Infrastructure for development : a policy agenda for Jamaica - UWI. Engineering Institute (IDB [S.l.], 1996)
Identifies the options for public sector modernization with special reference to infrastructure, notably electricity, roads, airports, seaports, water and sanitation and waste management. Focuses on questions of management financing and the regulatory environment with the objective of proposing an approach towards improving the infrastructure.